Ohne Bibel geht es nicht: vom Lesen, Lieben und Leben der Bibel (Why the Bible is necessary) - Deines, Roland (2010)
Three papers given in German for a wider audience in the summer of 2010. The first lecture describes why people expect to hear God's voice when they read the Bible; the second deals with Pope Benedict's XVI book on »Jesus of Nazareth«; and the third and final lecture is devoted to the question of salvation history.